2020
DOI: 10.1503/jpn.190038
|View full text |Cite
|
Sign up to set email alerts
|

Frontoparietal and salience network alterations in obsessive–compulsive disorder: insights from independent component and sliding time window analyses

Abstract: Background: Resting-state functional MRI (fMRI) studies commonly report alterations in 3 core networks in obsessive-compulsive disorder (OCD) -the frontoparietal network, the default mode network and the salience network -defined by functionally connected infraslow oscillations in ongoing brain activity. However, most of these studies observed static functional connectivity in the brains of patients with OCD. Methods: To investigate dynamic functional connectivity alterations and widen the evidence base toward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 40 publications
1
16
0
Order By: Relevance
“…As previous studies did not use the same indicators to assess the dynamic characteristics of functional networks in patients with OCD, direct comparisons between previous findings and ours were excluded. One study of OCD based on dFNC showed more changes during the time course of dynamic functional connection in patients when compared with HC 14 . However, this study did not quantify this dynamic change.…”
Section: Discussionmentioning
confidence: 67%
See 4 more Smart Citations
“…As previous studies did not use the same indicators to assess the dynamic characteristics of functional networks in patients with OCD, direct comparisons between previous findings and ours were excluded. One study of OCD based on dFNC showed more changes during the time course of dynamic functional connection in patients when compared with HC 14 . However, this study did not quantify this dynamic change.…”
Section: Discussionmentioning
confidence: 67%
“…However, the mechanism involved in the dynamic functional network of OCD in abnormal repetitive behavior and thinking remains unclear. To the best of our knowledge, only one study on dFNC in OCD has been published, which showed more changes in the time course of dynamic functional connection in patients than in healthy controls (HC) 14 . However, this study did not quantify this dynamic change and did not rule out the influence of drug therapy on the results.…”
mentioning
confidence: 78%
See 3 more Smart Citations